The Anglican eucharist in Australia: the history, theology, and liturgy of the eucharist in the Anglican Church of Australia - Douglas, Brian (Anglican-Episcopal theology and history, 2021)
Acknowledgements IX -- Abbreviations X -- 1 A Multiformity of Assumptions in the Anglican Church of Australia -- 1 The Anglican Church of Australia -- 2 The Notion of Sacramentality -- 3 Philosophical Assumptions -- 4 Overview of This Book -- 2 The Colonial Period in Australia, 1788-1829 -- 1 The Coming of the First Fleet and the First Eucharist -- 2 Johnson's Understanding of the Eucharist -- 3 Johnson's Evangelical Heritage -- 4 Johnson's Appointment as Chaplain -- 5 Sacramentality? -- 6 The 1662 Book of Common Prayer and Eucharistic Theology -- 7 Public Worship in the Early Penal Colony -- 3 Broughton and the Growth of the Church of England in Australia 1829-1860 -- 1 Broughton Influenced by Tractarianism -- 2 Defections to Rome: Robert Knox Sconce and Thomas Cooper Makinson -- 3 Militant Protestants: Peter Beamish and Francis Russell -- 4 Bishop Broughton's Innovations in Worship -- 5 Other Bishops -- 6 Broughton's Successor - Bishop Barker -- 4 The Eucharistic and Sacramental Theology of the Colonial Bishops -- 1 The Bishops and Differing Sacramental Theologies -- 2 The Bishop's Conference of 1850 -- 3 William Grant Broughton - Bishop of Sydney -- 4 Charles Perry, Bishop of Melbourne -- 5 Francis Nixon, Bishop of Tasmania -- 5 Eucharistic Theology in Significant Parishes in the Diocese of Sydney -- 1 St James King Street, Sydney -- 2 Christ Church St Laurence, Sydney -- 6 Party Division 1860-1960 -- 1 Party Division -- 2 The Diocese of Sydney - Two Significant Parishes Continued -- 3 The Diocese of Adelaide -- 4 The Diocese of Melbourne -- 5 St Peter's Eastern Hill, Melbourne -- 6 The Province of Queensland -- 7 Other Dioceses -- 8 Impetus for Revision -- 9 Alternatives to the 1662 Book of Common Prayer -- 10 The 1928 Book of Common Prayer -- 11 Departures from the Use and Theology of the 1662 BCP -- 12 Conclusion -- 7 Preparing for An Australian Prayer Book -- 1 Moving towards a Prayer Book -- 2 English Series 1 -- 3 English Series 2 -- 4 English Series 3 -- 8 The Beginnings of Prayer Book Revision in Australia -- 1 Trial Uses and the Constitution -- 2 1966 Report of the Prayer Book Commission of the Church of England in Australia -- 3 A Liturgy for Africa -- 4 A Service of Holy Communion for Australia, 1969 (Australia, '69) -- 5 Sunday Services Revised, 1972 -- 6 A Service of Holy Communion for Australia, 1973 (Australia '73)